Analysis Types of Code Mixing used from the Ruang Sandi Podcast Video with Cinta Laura - Prameswari, Dinda Fitri; Angelin, Sheva; Tsalits, Widya Nabbila (Universitas Negeri Padang, 2024)
This research focuses on Code Mixing Analysis in Sandi's Podcast with Cinta Laura. This research purposes to describe the types of code mixing and its occurrence. The method of this research is descriptive qualitative analysis to analyze the data. The research data collected from Sandi's YouTube channel entitled Podcast Room with High Motivation Love Achieves Many Things at a Young Age, Sandi Uno